Apportionment of sources of heavy metals to agricultural soils using isotope fingerprints and multivariate statistical analyses. (June 2019) - Wang, Pengcong; Li, Zhonggen; Liu, Jinling; Bi, Xiangyang; Ning, Yongqiang; Yang, Shaochen; Yang, Xiaojing
Abstract: Apportioning sources of environmental pollutants is key to controlling pollution. In this study, the sources of heavy metals to 234 agricultural soils from the Jianghan Plain (JHP) (∼22454 km 2 ) in central China were discriminated between using Cd and Pb isotope compositions and multivariate statistical analyses. Concentrations of some metals in JHP soils (0.48 ± 0.2, 48.2 ± 15.9, 0.12 ± 0.23, 48.8 ± 16.4, 36.5 ± 9.8, and 96.8 ± 42.2 mg kg −1 for Cd, Cu, Hg, Ni, Pb, and Zn, respectively) were higher than background concentrations in Chinese soil. The Cd isotope compositions for the JHP soils (δ 114/110 Cd values −0.76‰ to −0.25‰) were similar to Cd isotope compositions found for smelter dust and incinerator fly ash, indicating Cd was supplied to the JHP soils by ore smelting and/or refining processes. The Pb isotope compositions for the JHP soils ( 206 Pb/ 207 Pb 1.182–1.195 and 208 Pb/ 206 Pb 2.078–2.124) were between the Pb isotope compositions found for Chinese coal and natural sources, which a binary isotope mixing model indicated contributed 52% and 48%, respectively, of the Pb in JHP soils. Cluster analysis and positive matrix factorization indicated that the sources of heavy metals in JHP soils may consist of smelting and/or refining activities, coal combustion, agricultural activities, and natural sources (including Han River sediment and soil parent materials). The isotope fingerprints and multivariate statistical analyses together indicated that coal combustion and smelting and/or refining activities were the main anthropogenic sources of heavy metals polluting JHP soils. Graphical abstract: Image 1 Highlights: Multivariate statistics and isotope were used together to trace the pollution. Limited contribution of agricultural activities to heavy metals in the soils. Coal combustion and smelting/refining activities were main anthropogenic sources.